CLINICAL STUDY FOR THE OBSERVATION OF EPIDEMIOLOGICAL TRENDS IN PEPTIC ULCER PERFORATION - Muhammad Rehman Gulzar; Umer Farooq; Salman Azeem; Ahmad Azeem (Journal of University Medical & Dental College, 2019)
OBJECTIVE: To observe the Epidemiological Trends of perforated Peptic ulcer disease. STUDY DESIGN: Retrospective Analytical Study. DURATION OF STUDY: October 2016 to February 2018.(16 months) SETTING: Department of surgery, Liaquat ward, DHQ Teaching Hospital Faisalabad. METHODOLOGY: Over a period of 16 months, 50 cases of peptic ulcer perforation were reported and managed in surgical emergency Department. Record of all these cases was preserved in the form of history, Lab reports and operation notes. Data was then analyzed, interpreted and observed for Age distribution, Gender distribution, Socioeconomic status, History of peptic ulcer disease, History of NSAIDS intake ,Smoking Habits, Urban and Rural and Air under diaphragm. RESULTS: Age distribution shows that peptic ulcer perforation is prevailing disease in age >60 years with 38%, 78% of patients were male giving a male to female ratio of 4:1, Lower socioeconomic class was more aﬀected ( 60%), Mostly patients had a history of peptic ulcer disease (70% of the cases). 57% of the patients were smokers,28% patients were taking NSAID , 60% were urban patients and Air under diaphragm was observed in 85 % of the cases. CONCLUSION: It was concluded that elderly people with age more than 60 years with a previous history of peptic ulcer disease and NSAID intake , specially males of urban lower class are aﬀected by peptic ulcer perforation disease in our study.